2019
DOI: 10.20944/preprints201901.0308.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lightweight Cipher for H.264 Videos in the Internet of Multimedia Things with Encryption Space Ratio Diagnostics

Abstract: Within an Internet of Multimedia Things, the risk of disclosing streamed video content, such as arising from video surveillance, is of heightened concern. This leads to the encryption of that content. To reduce the overhead and lack of flexibility arising from full encryption of the content, a good number of selective-encryption algorithms have been proposed in the last decade. Some of them have limitations, in terms of significant delay due to computational cost, or excess memory utilization, or, despite bein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Within an IoT, it is possible that pre-processing using imageprocessing techniques on video frames might take place locally, while once features were extracted, images with reduced data could be sent over a wireless network. The authors have previously investigated [54] lightweight encryption for privacy protection of video communicated over IoMT networks. Ultimately, that can take place once the feasibility of pupillometry and the scale and structure of data processing Subjects were instructed to avoid unnecessary eye and head movement during the data collection phase.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…Within an IoT, it is possible that pre-processing using imageprocessing techniques on video frames might take place locally, while once features were extracted, images with reduced data could be sent over a wireless network. The authors have previously investigated [54] lightweight encryption for privacy protection of video communicated over IoMT networks. Ultimately, that can take place once the feasibility of pupillometry and the scale and structure of data processing Subjects were instructed to avoid unnecessary eye and head movement during the data collection phase.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…In [28], the authors developed a lightweight encryption system by applying extended permutation with exclusive OR on the syntax elements. The final phase of the encoding generated selected syntax elements.…”
Section: Related Studiesmentioning
confidence: 99%
“…At this substitution stage, usually reversible operations, such as XOR, are used. The XOR-based encryption process is employed to change the pixel values for enhancing the cryptography performance of the introduced video security technique through XOR-ing the frame pixels with the key's bits [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results demonstrated that the presented ROIbased HEVC ciphering algorithm can be performed for real-time security applications with achieving miniature complexity expenses and transmission bitrate. In [39], a lightweight IoMT-based selective encryption algorithm for H.264 video communication is proposed. This algorithm encrypts the chosen syntax video components with the exclusive OR (XOR) based on an extended permutation process.…”
Section: Review Of Related Workmentioning
confidence: 99%